Make investment scaling-up work in Benin : a macro-fiscal analysis - Barhoumi, Karim; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2016)
This paper conducts a systematic growth and fiscal analysis to determine: (1) the growth potential of Benin's ambitious scaling-up of investment, and (2) how the government can generate the necessary fiscal space needed to increase investment without jeopardizing Benin's solid macroeconomic performance.
Chapter 1. Growth performance and constraints -- Chapter 2. The macro-fiscal impact of scaling-up public investment -- Chapter 3. Creating the fiscal space for successful scaling-up -- Conclusion and policy discussions
Includes bibliographical references (p. 33-34)
Keywords: Investment and investments; INVESTMENTS; PUBLIC INVESTMENT; SUSTAINABLE DEVELOPMENT; ECONOMIC DEVELOPMENT; TAX REVENUES; Fiscal space; ECONOMIC CONDITIONS; BENIN